2020
DOI: 10.1371/journal.pcbi.1007835
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous emergence of connectivity assemblies via spike triplet interactions

Abstract: Non-random connectivity can emerge without structured external input driven by activitydependent mechanisms of synaptic plasticity based on precise spiking patterns. Here we analyze the emergence of global structures in recurrent networks based on a triplet model of spike timing dependent plasticity (STDP), which depends on the interactions of three precisely-timed spikes, and can describe plasticity experiments with varying spike frequency better than the classical pair-based STDP rule. We derive synaptic cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 128 publications
(259 reference statements)
3
37
0
Order By: Relevance
“…It is not completely clear, however, what exactly drives the formation of assemblies in the brain. It has been recently proposed that correlated input could drive assembly formation even in the absence of rate-based plasticity mechanisms [6] and that assemblies could also form spontaneously in the absence of structured external stimulation [7]. Future work could extend our current analysis and form silent EI assemblies without the transient increase in mean firing rate by stimulation of assembly neurons.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is not completely clear, however, what exactly drives the formation of assemblies in the brain. It has been recently proposed that correlated input could drive assembly formation even in the absence of rate-based plasticity mechanisms [6] and that assemblies could also form spontaneously in the absence of structured external stimulation [7]. Future work could extend our current analysis and form silent EI assemblies without the transient increase in mean firing rate by stimulation of assembly neurons.…”
Section: Discussionmentioning
confidence: 70%
“…How exactly cell assemblies are formed and how their synapses and firing activity encode information, however, is yet to be fully understood. Theoretical work [2][3][4][5][6][7][8] has shown it is possible to create such assemblies by combining different forms of synaptic plasticity. In some of these models [3,4], when strongly connected assemblies are formed, spontaneous activity is characterized by an overall stable firing rate across the excitatory population, but with the firing rate of individual assemblies transitioning between periods of high and low activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have analysed the development of mainly excitatory networks with spike-timing dependent plasticity under spontaneous activity, and some speculated on its impact on sequence memory: Analytical studies showed that STDP can autonomously develop feed-forward structures [Ocker et al, 2015, Ravid Tannenbaum and Burak, 2016, Montangie et al, 2020]. Numerical studies confirm this result: Networks equipped with STDP and a form of synaptic normalisation converge to form multiple synfire chains under both sequence and noise input [Fiete et al, 2010, Weissenberger et al, 2017].…”
Section: Discussionmentioning
confidence: 97%
“…Higher order interactions are at the heart of triplet rules [47,[68][69][70], and other types of interactions may also be important, e.g. for calcium-based update rules [71,72].…”
Section: Network Modelmentioning
confidence: 99%
“…In particular, Ravid Tannenbaum et al showed that in networks of Poisson neurons synfire chains and self connected assemblies can emerge autonomously in recurrent networks [46]. Montangie et al showed that a more realistic form of STDP based on spike triplets also leads to autonomous emergence of assemblies [47].…”
Section: Introductionmentioning
confidence: 99%